2005
DOI: 10.1021/cg050050l
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Tetraphenol and Its Complexes with Aromatic Diamines:  Novel Interpenetrating and Noninterpenetrating Organic Assemblies

Abstract: The solid-state self-assembly of tetraphenol 1 and its complexes with 4,4′-bipyridine (bpy), trans-1,2-bis(4-pyridyl)ethylene (bpy-ethe), and 1,2-bis(4-pyridyl)ethane (bpy-etha) is reported. Forces such as O-H‚‚‚N, O-H‚‚‚O and weak interactions prevalent in the structures promote the formation of interpenetrating and noninterpenetrating supramolecular assemblies. The crystal structure of tetraphenol 1 is characterized by the formation of hydrogen-bonded eight-membered cyclic structures. A diamondoid network wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Triphenol 1 crystallizes into ladder-type networks held together by O−H···O hydrogen bonds (Figure a). The packing of the molecule in 3D is similar to the previously reported trisphenols 10a. The lattice of 1·pyz is characterized by a ladder structure formed via the interplay of C−H···O and O−H···N bonds.…”
Section: Comparison Of the Packing Motifssupporting
confidence: 75%
See 3 more Smart Citations
“…Triphenol 1 crystallizes into ladder-type networks held together by O−H···O hydrogen bonds (Figure a). The packing of the molecule in 3D is similar to the previously reported trisphenols 10a. The lattice of 1·pyz is characterized by a ladder structure formed via the interplay of C−H···O and O−H···N bonds.…”
Section: Comparison Of the Packing Motifssupporting
confidence: 75%
“…Synthesis. A previously reported procedure was used for the synthesis of target triphenol 1 . The synthetic route is shown in Scheme .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Although many of the interpenetrated structures that have been reported involve metal-organic frameworks, there are also examples involving hydrogen bonded networks. [3][4][5][6] The assembly of solid state structures through hydrogen bonds is an extremely topical area of chemistry. 7 In one of the best illustrations of crystal engineering, Ward and co-workers have shown that guanidinium cations and sulfonate anions assemble through hydrogen bonds into hexagonal sheets, 8,9 and by using disulfonates these sheets can be connected into three-dimensional arrays with predictable structures.…”
mentioning
confidence: 99%